Process evaluation for enhanced production of aflatoxin-free citric acid by food-grade Aspergillus niger - Ambreen Latif; Hazrat Ali; Muhammad Bilal Khan Niazi; Zaib Jahan; Noor Hassan; Iqra Latif Ghuman; Abdul Tawab; Anam Saqib; Muhammad Hamid Rashid (PLoS ONE, 2025)
Aspergillus niger is considered as the main horsepower for the production of 90% of citric acid worldwide. Citric acid is produced under submerged fermentation and the process yield depends on A. niger and the process parameters. The current research work was aimed to evaluate the most favorable process parameters for producing the highest amount of citric acid using A. niger. The process parameters such as sucrose concentration, pH, temperature, and inoculum size were evaluated for determining their impact on citric acid production. High-performance liquid chromatography (HPLC) analyses revealed different optimal conditions for citric acid production. The optimal conditions found for higher yield of citric acid by A. niger included sucrose concentration 12.0% (w/v), temperature 30 °C, pH 5.0 and an inoculum size of 5.0% (v/v). At these optimal conditions, the resulting concentration was 59.0 g/l of citric acid, 24.0 g/l of biomass production, and 2.0 g/l of residual sugar. In addition, food-grade nature of A. niger was determined by investigating aflatoxin in production media using HPLC. Our results showed that there were no traces of aflatoxins in the production media, hence the used A. niger was of food-grade nature. These findings underline the importance of process evaluation for maximizing citric acid yield and efficiency of A. niger for bioprocess engineering and industrial applications.